Inhibition of α-glucosidase activity by selected edible seaweeds and fucoxanthin - Nazikussabah, Zaharudin; Staerk, Dan; Dragsted, Lars Ove (Elsevier Ltd, 2019)
A 5 mg/mL solution of water, methanol and acetone extracts of seaweeds were used for α-glucosidase inhibition assay hyphenated with high performance liquid chromatography–mass spectrometry (HPLC–HRMS). The results showed acetone extracts of Undaria pinnatifida has the strongest inhibitory effect against α-glucosidase activity with IC50 0.08 ± 0.002 mg/mL. The active compound found in Undaria pinnatifida was identified as fucoxanthin. Analytical standard sample of fucoxanthin significantly inhibited α-glucosidase with IC50 value 0.047 ± 0.001 mg/mL. An inhibition kinetics study indicates that fucoxanthin is showing mixed-type inhibition. These results suggest that Undaria pinnatifida has a potential to inhibit α-glucosidase and may be used as a bioactive food ingredient for glycaemic control.